Meta-Capitalism and Ecological Threats in Indonesia: A Postcolonial Study of the Indonesia Emas 2045 Discourse - Tampilang, Risno (SERUNAI, 2025)
This article examines the narrative of “Towards Golden Indonesia 2045” within the framework of postcolonial studies by highlighting the threat of meta-capitalism to Indonesia’s ecology. Meta-capitalism is an advanced form of global capitalism that not only exploits natural resources materially, but also dominates discourse, policies, and social structures. Through a qualitative approach with postcolonial analysis, this study shows that the narrative of sustainable development packaged in the spirit of “Golden Indonesia” actually contains ecological and social paradoxes. This narrative often justifies the penetration of foreign capital and extractive policies that harm local communities and exacerbate structural inequality. This study offers an “ecological triage” approach as a form of resistance to meta-capitalism, namely through emergency conservation, ecological restoration, and advocacy of sustainable policies. This article recommends the need for a reformulation of Indonesia’s development paradigm by emphasizing ecological justice, local independence, and deconstruction of capitalist ideology in national developmen